CARTE HEURISTIQUE COMME STRATÉGIE DE BROUILLONNAGE: QUEL IMPACT SUR LA COHÉRENCE TEXTUELLE? - Marko Nikolic (European Scientific Journal, ESJ, 2014)
Mind map is a learning and organization tool whose effectiveness has been demonstrated in many disciplines.However, there have been few studies about its efficiency as a pre-writing activity. This research focuses on the use of Mind Mapping as a drafting strategy in the second language written production, and examines its impact on the coherence of produced texts. According to this study, the writers' ability to produce coherent texts does not directly depend on their second language proficiency. Mind mapping as a drafting strategy, although it has no significant impact on the coherence of written texts (p = 0.067), appears to be more appreciated and better received by students who are better able to structure their ideas and produce coherent texts. It remains to be seen whether there is a link between the writers' ability to produce coherent Mind Maps and their ability to produce coherent texts.